PEMBARUAN HUKUM WARIS ISLAM DI INDONESIA - Muhibbuddin, Muhammad (Ahkam: Jurnal Hukum Islam, 2015)
This article discusses one of the agenda reforming Islamic law aboutinheritance for the descendant of different religion. According to theDecree of the Supreme Court Number: 368 K/AG/1995 on and numberNomor: 51 K/AG/1999 it is possible for non muslim descendants toreceive inheritance through wajibah.Kata kunci: Pembaruan, Hukum Waris Islam